Jakarta Waterfront City Development - Sidarta, Moch (Journal of Regional and City Planning, 1996)
The Jakarta Waterfront City Development is a mission to revitalize and develop the waterfront of Jakarta and to resume its place as the front door to the city and the nation. To support this development, the government of Indonesia has issued the Presidential Decree (KEPRES) which designated the boundaries of the waterfront area and established the Jakarta Waterfront Implementation Board. The waterfront city which covers an area of approximately 5000 ha.,2700 ha of which will come from land reclamation, will be developed through some stages and by cooperation between the government public and private sectors.